2012
DOI: 10.5194/hessd-9-4505-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COSMOS: The COsmic-ray Soil Moisture Observing System

Abstract: Abstract. Area-average soil moisture at the sub-kilometer scale is needed but until the advent of the cosmic-ray method (Zreda et al., 2008), it was difficult to measure. This new method is now being implemented routinely in the COsmic-ray Soil Moisture Observing System (or COSMOS). The stationary cosmic-ray soil moisture probe (sometimes called "neutronavka") measures the neutrons that are generated by cosmic rays within air and soil, moderated by mainly hydrogen atoms located primarily in soil water,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
135
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(136 citation statements)
references
References 34 publications
(27 reference statements)
0
135
0
1
Order By: Relevance
“…chemically defended leaves). However, to provide some guidance as to the potential frequency of water-mediated top-down effects, we examined volumetric soil moisture measurements across the United States (US) using the COSMOS Soil Moisture Network database [48] and found that soil moistures below 6.81% can be found in 49% of the 65 US measurement locations, over the 7 year period from 2008 to 2014-even mesic locations in the southeastern US and in northern Wisconsin and Michigan showed values below this threshold, but the greatest frequency was within the US sunbelt (electronic supplementary material, figure S5). These results correspond well to previous suggestions that patterns of animal species richness are at least partially limited by water at all but the highest latitudes (energy only at more than 508; [7]).…”
Section: Discussionmentioning
confidence: 99%
“…chemically defended leaves). However, to provide some guidance as to the potential frequency of water-mediated top-down effects, we examined volumetric soil moisture measurements across the United States (US) using the COSMOS Soil Moisture Network database [48] and found that soil moistures below 6.81% can be found in 49% of the 65 US measurement locations, over the 7 year period from 2008 to 2014-even mesic locations in the southeastern US and in northern Wisconsin and Michigan showed values below this threshold, but the greatest frequency was within the US sunbelt (electronic supplementary material, figure S5). These results correspond well to previous suggestions that patterns of animal species richness are at least partially limited by water at all but the highest latitudes (energy only at more than 508; [7]).…”
Section: Discussionmentioning
confidence: 99%
“…Further information of such advances can be found in a number of synthesis papers devoted to some of these techniques (e.g., Robinson et al, 2008;Zreda et al, 2012).…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…Z kolei Hendrick i Edge wykazali, że intensywność "szybkich" neutronów nad powierzchnią ziemi zależy od zawartości wilgoci w glebie [5], co zostało wykorzystane do jej pomiaru [6,7]. Wodór posiada największą siłę hamowania i usuwania neutronów [1,8], co stanowi podstawę pomiaru wilgotności gleby metodą neutronów kosmogenicznych. Większa ilość wody w glebie skutkuje większym wyhamowaniem neutronów, powodując zmniejszenie ich ilości nad jej powierzchnią.…”
Section: Wprowadzenieunclassified